Electrical and magnetic property of Al62Cu25.5Fe 12.5 icosahedral quasicrystal: Spin-orbit scattering - Ray M.K.; Bagani K.; Ghosh B.; Sardar M.; Banerjee S.; Srivastava V.C.; Mukhopadhyay N.K. (My University, 2025)
We report here electrical and magnetic properties of Al62Cu 25.5Fe12.5 icosahedral quasicrystal. We have measured the electrical resistivity from 2K to 300K and observed negative temperature coefficient of resistivity above 15K. Below 15K we see a decrease in resistivity showing maxima around 15K. Upon application of a high magnetic field of 5 Tesla the maxima disappears and below 15 K the resistivity rises sharply. Magnetoresistance was measured at various temperatures as a function of applied field and we observe positive magnetoresistance for all temperatures. We have attributed these effects arising due to spin-orbit scattering. © 2013 American Institute of Physics.